Vascular superoxide production by NAD(P)H oxidase: association with endothelial dysfunction and clinical risk factors. - Guzik, T; West, N; Black, E; McDonald, D; Ratnatunga, C; Pillai, R; Channon, K (2000)
Superoxide anion plays important roles in vascular disease states. Increased superoxide production contributes to reduced nitric oxide (NO) bioactivity and endothelial dysfunction in experimental models of vascular disease. We measured superoxide production by NAD(P)H oxidase in human blood vessels and examined the relationships between NAD(P)H oxidase activity, NO-mediated endothelial function, and clinical risk factors for atherosclerosis. Endothelium-dependent vasorelaxations and direct measurements of vascular superoxide production were determined in human saphenous veins obtained from 133 patients with coronary artery disease and identified risk factors. The predominant source of vascular superoxide production was an NAD(P)H-dependent oxidase. Increased vascular NAD(P)H oxidase activity was associated with reduced NO-mediated vasorelaxation. Furthermore, reduced endothelial vasorelaxations and increased vascular NAD(P)H oxidase activity were both associated with increased clinical risk factors for atherosclerosis. Diabetes and hypercholesterolemia were independently associated with increased NADH-dependent superoxide production. The association of increased vascular NAD(P)H oxidase activity with endothelial dysfunction and with clinical risk factors suggests an important role for NAD(P)H oxidase-mediated superoxide production in human atherosclerosis. The full text of this article is available at http://www.circresaha.org.